IDENTIFIKASI SINGLE NUCLEOTIDE POLYMORPHISM (SNP) PADA GEN HEAT SHOCK PROTEIN 70 (HSP70) AYAM KUB (KAMPUNG UNGGUL BALITBANGTAN) - Ridhwan Ahmad Karyana, - (2023)
Global warming is defined as a form of ecosystem imbalance on earth caused by the process of increasing the average temperature of the atmosphere, sea and land on earth. Global warming has an impact, one of which is the presence of heat stress in poultry, one of which is in chickens. The HSP70 gene has a function that can play a role in regulating protein folding and can be protected from damage caused by heat stress. The purpose of this study was to analyze HSP70 gene polymorphism in Balitbangtan superior native chickens (KUB) in the area coding and 3'UTR. The method used in this study used 10 KUB chicken DNA samples which were carried out in stages, namely PCR amplification, electrophoresis, sequencing quantification test, and data processing with two applications, namely bioedit and MEGA. The results of the qualitative test showed that 10 samples with 10 samples got good results because they could be seen on the UV transimulator, namely samples R1, R2, R3, R4, R5, R6, R7, R9, R17, and R33. The results of the BLAST test on KUB chickens had a similarity of more than 95% in each sample to the HSP70 Gallus gallus gene. The selection of three DNA samples for sequencing for each primer, namely samples R7, R9, and R17, was due to the good results obtained from electrophoresis. The results of this study found 12 SNPs namely in positions 421G>C, 425C>G, 501G>C, 693A>G, 717C>A, 728G>A, 748 G>C, 767A>T and 821G>,1476T>C, 2194T>A and 2195A>T. The conclusion obtained is the discovery of information about the existence of the HSP70 gene polymorphism in KUB chickens as a database for the development of heat stress markers in local Indonesian chickens.